Use of Selected Essential Oils for Controlling Stem-end Rot Disease in Mango (cv. Karuthacolomban) - Anjali A. Kulasinghe; K.O.L. Chathurika karunanayake; S. Somarathne (The Open University of Sri Lanka, 2019)
In Sri Lanka, stem-end rot (SER) caused by Lasiodiplodia sp. is the most common and serious disease that affects the mango cv. 'Karuthacolomban'. At present, disease control is achieved with chemical fungicides which are hazardous to human health and environment. As such, this research looked into the possibility of using essential oils (EOs) as biological fungicides against Lasiodiplodia sp. in mango (cv. Karuthacolomban). Pure-grade Basil oil (Ocimum basilicum), Cardamom oil (Elettaria cardamomum), Citronella oil (Cymbopogon nardus L.), Lemon oil (Citrus limon), Mustard oil (Brassica juncea) and Orange oil (Citrus sinensis) were selected for the study. The most effective EOs against Lasiodiplodia sp. under in vitro conditions selected by a poisoned food bio-assay, were used in in vivo studies. The effect of the treatment on reducing disease development, organoleptic properties and the edibility of fruits after in vivo application was assessed. Twenty-four hours after artificial inoculation, fruits were dipped in the selected concentration of the EO solutions at room temperature or at 45˚C for 3 minutes and then stored under ambient conditions. Disease development, percentage weight loss, titrable acidity and total soluble solids contents were measured and a sensory evaluation with a taste panel was also carried out for the treated fruits. Results revealed that basil, cardamom (700 μl l-1) and citronella (400 μl l-1) oils significantly reduced the growth of Lasiodiplodia sp. under in vitro conditions and cardamom oil (700 μl l-1) in warm water effectively reduced the severity of SER under in vivo conditions with no effect on sensory properties or physico-chemical quality parameters. Thus, plant EOs can serve as safe, eco-friendly and effective alternatives to synthetic fungicides.